Functionalized Lignin for Fabrication of FeCoNi Nanoparticles‐Enriched 3D Carbon Hybrid: From Waste to a High‐Performance Oxygen Evolution Reaction Catalyst. Issue 13 (13th July 2022) - Min, Xiaoye; Zhang, Tingzheng; Xie, Mingbo; Zhang, Kejing; Chai, Liyuan; Lin, Zhang; Ding, Chunlian; Shi, Yan
Abstract: The application of lignin‐derived carbon materials in energy conversion is hindered by the complex molecular structure and few metal coordination sites of lignin. In this work, a simple oxidation–coordination method was developed for scalable synthesis of a FeCoNi nanoparticles‐modified nitrogen‐doped carbon hybrid (designated as O−FeCo40 Ni10 −C) with lignin as carbon precursor for oxygen evolution reaction (OER). Specifically, a Fenton reaction‐driven pre‐oxidation process changed the molecular structure of alkali lignin and increased functional groups, which contributes to the efficient incorporation of metal active sites into lignin‐derived carbon materials. Benefiting from abundant active sites, the synergistic effect of CoFe/NiFe compositions and interconnected porous structure, the obtained O−FeCo40 Ni10 −C exhibited a high OER activity. It only required an overpotential of 280 mV to drive current densities of 10 mA cm −2 in 1 M KOH solution. Moreover, the turnover frequency of O−FeCo40 Ni10 −C was 0.030 and 0.185 s −1 at the overpotential of 300 and 400 mV, respectively. This work provided an environmentally‐friendly strategy to synthesize lignin‐derived catalyst for OER and expanded the application of lignin in energy conversion filed. Abstract : A lignin‐derived FeCoNi‐enriched nitrogen‐doped carbon hybrid (O−FeCoNi−C) was synthesized by an oxidation–coordination method. Specifically, a Fenton process was applied as pretreatment to change the molecular structure of alkali lignin, which contributes to the efficient incorporation of metal active sites into lignin‐derived carbon materials. The increased metal active sites in O−FeCoNi−C guarantee the excellent electrochemical performance as an OER material.